Fracturing a dysfunctional Edwards Perimount bioprosthetic valve to facilitate percutaneous valve‐in‐valve placement of SAPIEN 3 valve with modified delivery system. Issue 1 (10th October 2017) - Shahanavaz, Shabana; Rockefeller, Toby; Nicolas, Ramzi; Balzer, David
Abstract: Pulmonary valve replacement via surgical implantation of a bioprosthetic valve (BPV) is a well‐established treatment for patients with dysfunctional RV outflow tracts. BPVs are prone to structural deterioration, and will eventually require replacement. Recently, percutaneous valve‐in‐valve (VIV) placement of transcatheter valves has established itself as a safe and effective alternative to surgical revision. Unfortunately, VIV therapy is inherently limited by the inner diameter of the BPV, which restricts the number of eligible patients. Other centers have reported on the feasibility of cracking certain BPVs with ultra high‐pressure balloons in bench testing. We now report cracking an Edwards Perimount BPV in the pulmonary position to facilitate VIV placement of an Edwards SAPIEN 3. The ability to crack the Perimount valve allowed placement of a larger valve than previously considered and minimized the final valve gradient. In an effort to avoid the morbidity and mortality of surgical pulmonary valve replacement, this new strategy will expand the number of patients eligible for percutaneous VIV therapy.